The influence of workload and compensation on employee performance at Lopo Mandheling Coffee Panyabungan, Mandailing Natal Regency - Aminah, Nur; Ardiansyah, Muhammad; Fitri, Sari (Institute of Computer Science (IOCS), 2025)
The Influence of Work Environment and Compensation on Employee Performance at Lopo Mandheling Coffee Panyabungan Mandailing Natal Regency. The problem in this research is, first, working in a cafe that is open every day can become a burden for the employees. Second, the division of work that does not match the employees' work capacity results in an increase in the workload borne by the employees. Third, the provision of salaries to employees that do not match their work results will impact employee performance at Lopo Mandheling Coffee Panyabungan, Mandailing Natal Regency. This research aims to determine the effect of Work Discipline and Compensation on Employee Performance at Lopo Mandheling Coffee Panyabungan, Mandailing Natal Regency. The type of research used in this study is quantitative research. The data collection techniques used by the author are through observation and the distribution of questionnaires. This study involved a sample of 34 respondents. Work environment and compensation have a positive effect both partially and simultaneously on employee performance at Lopo Mandheling Coffee Panyabungan, Mandailing Natal Regency, with a t-value for the work environment variable (X1) of 1.875 and a t-value for the compensation variable (X2) of 1.777, with a t-table value of 1.696. The direction of the relationship is positive, which means that if the work environment and compensation are provided at a high level, the employee performance variable will also increase.